Physical and physiological characteristics of various-sided games in Elite Women`s Soccer - Mara, J. K.; Thompson, K. G.; Pumpa, K. L. (International Journal of Sports Physiology and Performance, 2016)
Purpose To investigate the physical and physiological response to different formats of various-sided games. Methods: Eighteen elite women`s soccer players wore 15-Hz global positioning system devices and heart-rate (HR) monitors during various-sided games (small, 4 vs 4 and 5 vs 5; medium, 6 vs 6 and 7 vs 7; large, 8 vs 8 and 9 vs 9). Results: Players covered more relative sprinting distance during large-sided games than in small-sided (P < .001, d = 0.69) and medium-sided (P < .001, d = 0.54) games. In addition, a greater proportion of total acceleration efforts that had a commencement velocity <1 m/s were observed in small-sided games (44.7% ± 5.5%) than in large-sided games (36.7% ± 10.6%) (P = .018, d = 0.94). This was accompanied by a greater proportion of acceleration efforts with a final velocity equivalent to the sprint threshold in large-sided games (15.4% ± 7.7%) than in small-sided games (5.2% ± 2.5%) (P < .001, d = 1.78). The proportion of time spent in HR zone 4 (>85% maximum HR) was greater during small-sided games (69.8% ± 2.5%) than in medium- (62.1% ± 2.8%, d = 2.90) and large-sided games (54.9% ± 3.1%) (P < .001, d = 5.29). Conclusions: The results from this study demonstrate that coaches can use small-sided games as an aerobic conditioning stimulus and to develop players` explosiveness and repeat-sprint ability over short durations. Large-sided games can be used to maintain aerobic capacity and develop maximum speed over longer distances.